Level Of Job Satisfaction Among Faculty In Saudi Arabia And Malaysia - Mahdi Arishi, Sultan Ahmed (2007)
The main purpose of this study was to investigate the level of satisfaction or dissatisfaction among faculty members in Saudi Arabia and Malaysia for comparative purposes and also for coming out with a thorough appraisal.